1997
DOI: 10.1093/ps/76.10.1337
|View full text |Cite
|
Sign up to set email alerts
|

Effects of beta-carotene and canthaxanthin on aflatoxicosis in broilers

Abstract: In 2 x 3 factorial experiments, 240 broiler chicks were fed diets containing 0, 0.01, and 0.02% beta-carotene or canthaxanthin with or without 5 ppm aflatoxin to determine the effects of these two carotenoids on the health and well-being of broilers subjected to aflatoxin poisoning. Neither beta-carotene nor canthaxanthin was effective at overcoming the growth-depressing effects of aflatoxin. Relative liver weights were significantly higher in broilers receiving dietary aflatoxin in the presence of beta-carote… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2001
2001
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 32 publications
0
12
0
Order By: Relevance
“…Several studies have demonstrated that canthaxanthin (the carotenoid used in the present experiment) is a potent antioxidant (Palozza & Krinsky, 1992;Surai et al, 2003) that may positively affect immune responses (Bendich & Shapiro, 1986;El-Hafeez et al, 2000;Chew & Park, 2004). But it has also been suggested that other carotenoids such as astaxanthin may exhibit stronger effects on oxidative stress (Miki, 1991;Woodall et al, 1996) and some studies have found weak or no effects of canthaxanthin on immunity (Sklan et al, 1989;Haq et al, 1996;OkotieEboh et al, 1997). However, in an earlier study (Ohlsson et al, 2003), we used food supplemented with carotenoids from Capsicum fruits containing an array of different carotenoids (Deli et al, 1996) and still found no effect on pheasant humoral immunity.…”
Section: Variation In the Effect Of Carotenoidsmentioning
confidence: 80%
“…Several studies have demonstrated that canthaxanthin (the carotenoid used in the present experiment) is a potent antioxidant (Palozza & Krinsky, 1992;Surai et al, 2003) that may positively affect immune responses (Bendich & Shapiro, 1986;El-Hafeez et al, 2000;Chew & Park, 2004). But it has also been suggested that other carotenoids such as astaxanthin may exhibit stronger effects on oxidative stress (Miki, 1991;Woodall et al, 1996) and some studies have found weak or no effects of canthaxanthin on immunity (Sklan et al, 1989;Haq et al, 1996;OkotieEboh et al, 1997). However, in an earlier study (Ohlsson et al, 2003), we used food supplemented with carotenoids from Capsicum fruits containing an array of different carotenoids (Deli et al, 1996) and still found no effect on pheasant humoral immunity.…”
Section: Variation In the Effect Of Carotenoidsmentioning
confidence: 80%
“…This means that bentonite had a clearly protective, antitoxic effect on the cyanide-fed rats, leading to lowered ALP levels. This was supported by Okotie -Eboh and Kubena [25] who reported that dietary addition of bentonite has been shown to reduce some toxic effects of some toxins and improve the performance of birds. Furthermore, some other studies showed also that bentonite has the ability to protect birds and other animals to some extent against the hepatoxicity of Aflatoxins [26,27,28,29].…”
Section: Discussionmentioning
confidence: 75%
“…The Scientific Committee on Food (SCF) issued an opinion on canthaxanthin in 1983 (EC, 1984), 1987(EC, 1989) and 1997(EC, 2000. The Scientific Committee on Animal Nutrition (SCAN) issued an opinion on the safety of canthaxanthin for salmon and trout, laying hens, and other poultry (EC, 2002).…”
Section: Regulation (Ec) No 1831/2003mentioning
confidence: 99%
“…The study published by Okotie-Eboh et al (1997) was considered instead. 32 The aim the study was to examine a potential beneficial effect of canthaxanthin on the toxicity symptoms caused by aflatoxin in chickens for fattening.…”
Section: Chickens For Fatteningmentioning
confidence: 99%
See 1 more Smart Citation